x2+7x+13=1

Move 1 to the left side of the equation by subtracting it from both sides.

x2+7x+13-1=0

Subtract 1 from 13.

x2+7x+12=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is 12 and whose sum is 7.

3,4

Write the factored form using these integers.

(x+3)(x+4)=0

(x+3)(x+4)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x+3=0

x+4=0

Set the first factor equal to 0.

x+3=0

Subtract 3 from both sides of the equation.

x=-3

x=-3

Set the next factor equal to 0.

x+4=0

Subtract 4 from both sides of the equation.

x=-4

x=-4

The final solution is all the values that make (x+3)(x+4)=0 true.

x=-3,-4

Solve using the Square Root Property x^2+7x+13=1